Comprehensive study of optical, photocatalytic and dielectric properties of Cd0.40Mn0.60ZnO2 annealed nanocomposites - Mansour Mohamed; A. Sedky; Abdullah F. Al-Naim; Abdullah Almohammedi; N. Afify (Scientific Reports)
Abstract The structural, optical, photocatalytic and dielectric properties of Cd0.40Mn0.60ZnO2 annealed nanocomposites prepared by Hydrothermal and subsequently annealed at temperatures between 200 °C and 600 °C. The particle size, crystallite size, and inter-plane separation were all enlarged with increased Tann at 600 °C and electrical dielectric loss increased. The specific surface area and photocatalytic activity were maximized, obtaining in this case a rate of degradation of 2 × 10-4s-1 at 400 °C. The lowest band gap = 1.55 eV was observed at 400 °C signifying enhanced optical absorption. The optical and dielectric properties exhibited a non-monotonic behavior: absorbance, optical dielectric loss, carrier density, dielectric constant, ac conductivity and Fill-factor, increased to the maximum values at 300 °C followed by a decrease. The dielectric constant (3.22), single and dispersion energies (10.58 eV and 23.33 eV), impedance (3.25–10.70 MΩ) and series resistance (14.3 MΩ) were maximum at 500 °C. From loss, modulus, and impedance curves, relaxation times were calculated by being 82.71 µs, 0.69–10.62 µs, and 15.92–40.94 µs. Two successive semicircles were identified in Cole-Cole plots for the composites after annealing in the range 200–500 °C. Results show composites annealed at 200–400 °C can be utilized for solar cell, supercapacitor, telecommunications, and water purification applications while those annealed at 500–600 °C are more suitable for a high frequency, nonlinear optical, and high-power antenna applications.